KOMUNIKASI SPIRITUAL DALAM TRADISI SEDEKAH SERABI DI EMPAT LAWANG, SUMATERA SELATAN - Yosepin, Pipin (Universitas Islam Negeri Mataram, 2021)
This article describes the socio-religious study of the existence of Islam and the local culture of the serabi alms tradition in Empat Lawang, South Sumatra. This research was studied through a phenomenological approach. In the tradition of sadaqah serabi, spiritual communication is established between the jurai tuo and the ancestors to form belief in the Creator. Exploration of the original belief in the Empat Lawang community indicates that there is a collective awareness that the intentions that are owned are mediated in the power of prayers from the ancestors through expressions of gratitude and vows that have been granted. Serabi charity proves that local culture has not changed after the entry of Islam. As a religion, Islam has empirically influenced, and even been accepted peacefully, to form the structure of the dimensions of human life in a socially and culturally dynamic manner.